Students’ Self-Confidence and Learning Motivation Toward English Speaking in EFL Context at SMA Negeri 1 Patimuan at Sidareja - Sri Hartati; Udi Samanhudi; Widya Rizky Pratiwi (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study investigates the interplay between student attitudes toward English language learning, self-confidence, and motivation within an Indonesian EFL context, focusing on SMA Negeri 1 Patimuan. Grounded in a qualitative descriptive framework, the research seeks to elucidate how students’ perceived self-efficacy and intrinsic and extrinsic motivations influence English speaking achievement, as well as the psychosocial and contextual factors shaping their learning trajectories. Data were collected through a triangulated approach comprising classroom observations, in-depth interviews with students and English teachers, and supporting documentary evidence (e.g., rubrics and learning artifacts), enabling a rich description of the dynamic relationship between affective factors and speaking performance in real classroom settings. Preliminary analyses indicate that higher self-confidence is associated with greater willingness to participate in speaking activities and higher intrinsic motivation, while lower self-confidence coincides with anxiety, avoidance of speaking opportunities, and reduced motivation. The findings underscore the interdependence of affective constructs and suggest that instructional interventions promoting supportive classroom climates, collaborative speaking activities, and constructive feedback can enhance both motivation and speaking proficiency. The study contributes to the literature on language learning psychology in Indonesian EFL contexts and offers practical guidance for curriculum design, teacher professional development, and guidance services aimed at fostering sustained motivation and confidence in English speaking among high school students.